Planta de tratamiento de agua potable del municipio de Barbosa (Santander) - Romero Rojas, Jairo Alberto; Quintero Sánchez, Rafael Yamid (Universidad Escuela Colombiana de Ingeniería Julio Garavito, 2016)
La PTAP de Barbosa tiene capacidad de tratar 120 L/s. En este artículo se confrontan los parámetros de diseño y operación con la normativa vigente, y se determina su conformidad con los parámetros de funcionamiento y las características de calidad del agua tratada.

Barbosa's WTP has the capacity to treat 120 l/s. In this article, the design and operational criteria are compared with current regulations and it is establizhed that the treatment plant meets the operationsl parameters and the characteristics of water quiality required.
Water treatment pñant of the municipality of Barbosa (Santander)
Keywords: Calidad del agua; Water quality; Agua potable; Drinking water; Plantas para tratamiento de agua; Water treatment plants; Evaluación operacional; Planta de tratamiento; Dosis óptima; Pautas de operación; Operational evaluation; Drinking water treatment plant; Optimal dose; Operation standards